Obstructive Sleep Apnea Syndrome is Associated with Metabolic Syndrome among Adolescents and Youth in Beijing - Xiao-Xue Qu; Issy C Esangbedo; Xiu-Juan Zhang; Shu-Jun Liu; Lian-Xia Li; Shan Gao; Ming Li (Chinese Medical Journal, 2015)
Background:. Obstructive sleep apnea (OSA) syndrome has a negative impact on the health of millions of adolescents and youth. The aim of this study was to evaluate the associations of OSA syndrome with obesity and cardiometabolic risk factors among adolescents and youth at risk for metabolic syndrome (MS). Methods:. A total of 558 subjects aged 14-28 years were recruited from the Beijing Child and Adolescent Metabolic Syndrome Study. Each underwent a 2-h oral glucose tolerance test (OGTT), echocardiography, and liver ultrasonography. Anthropometric measures, blood levels of glucose, lipids, and liver enzymes were assessed. Subjects with high or low risk for OSA were identified by Berlin Questionnaire (BQ). Results:. Among the subjects in obesity, 33.7% of whom were likely to have OSA by BQ. Subjects with high risk for OSA had higher neck and waist circumference and fat mass percentage compared to those with low risk for OSA (P < 0.001). Moreover, significant differences in levels of lipids, glucose after OGTT, and liver enzymes, as well as echocardiographic parameters were found between the two groups with high or low risk for OSA (P < 0.05). The rates of nonalcoholic fatty liver disease (71.0% vs. 24.2%), MS (38.9% vs. 7.0%), and its components in high-risk group were significantly higher than in low-risk group. Conclusions:. The prevalence of OSA by BQ was high in obese adolescents and youth. A high risk for OSA indicates a high cardiometabolic risk. Mechanisms mediating the observed associations require further investigation.